2019
DOI: 10.3390/urbansci3010019
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Researching Showering Routines: From the Individual to the Socio-Material

Abstract: In the UK, water supplies are under pressure from climate, population and lifestyle change. Showering is the largest component of domestic water consumption. Young adults are high water-users at a transitional life-stage, when practices are dynamic, and habits shaped. This paper presents the methodology, early findings and reflections on challenges of working with different data types and scales, to explore real-world water-saving through a mixed-methods approach, focusing on showering patterns of first year u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Therefore, universities wanting to adopt a greening strategy for campus life need to focus on developing awareness campaigns, which, in accordance with the findings of other studies [10,13,50,51,68,78], is crucial to the success of implementing sustainable consumption habits. Universities alone cannot implement extensive greening measures without coordinating their efforts with the utility services providers (water services, waste services, etc.)…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Therefore, universities wanting to adopt a greening strategy for campus life need to focus on developing awareness campaigns, which, in accordance with the findings of other studies [10,13,50,51,68,78], is crucial to the success of implementing sustainable consumption habits. Universities alone cannot implement extensive greening measures without coordinating their efforts with the utility services providers (water services, waste services, etc.)…”
Section: Discussionsupporting
confidence: 66%
“…These campaigns could also be carried out by involving the university management to identify some technical measures to optimize water consumption on campus (water faucet timers, economical shower heads, dual toilet tanks, etc.) and the dormitory management to help implement these solutions [50]. Another possibility is to introduce disciplines or new chapters in the existing curricula that target sustainable development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a UK-led national study, 32% of a sample of nearly 160,000 persons using EST's Water Energy Calculator reported an average shower length of 7.8 minutes (The Water Energy Calculator is an online tool that helps households in the UK understand the energy associated with water use in their home, and identify opportunities to manage their consumption and bills.) In the study by Simpson et al (2019), university students in campus accommodations in Bristol, UK, reported an average shower duration of 10-12 minutes, higher than reported UK norms.…”
Section: Shower Habits Conditioning Water Usementioning
confidence: 78%
“…A household water audit is used to assess the water usage behavior of respondents and how much water they are saving at home (Addo et al, 2018). By conducting a water audit (Master and Gandhi, 2017;Khedikar, 2011); (Gagnon, 1984), researchers estimate the water used in dishwashing, cloth washing, bathing (Kulkarni et al, 2014), showering (Simpson et al, 2019), car washing, flushing (Kubade et al, 2017), and in yards.…”
Section: Methodsmentioning
confidence: 99%